Investigating the introduction of a broadspectrum antiviral mechanism into grapevine - Wilsen, Kathleen L. (Kathleen Lucy) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2000.